Comparative clinical and sociodemographic assessment of substance use in first episode, drug-naïve psychosis and schizophrenia patients - Dağ, Demir Faruk; Uzun, Özcan (Journal of Dependence, 2025)
Objective: This study aims to compare recent-onset, drug-naïve patients with first-episode psychosis (FEP) and patients with schizophrenia in terms of substance and smoking history, and to explore their associations with sociodemographic and clinical characteristics. Methods: A total of 107 patients were included: 56 with drug-naïve FEP and 51 with schizophrenia. Standardized clinical instruments were used, including the Clinical Global Impression–Severity Scale (CGI-S), the Scale for the Assessment of Negative Symptoms (SANS), the Scale for the Assessment of Positive Symptoms (SAPS), and the Calgary Depression Scale for Schizophrenia (CDSS). Results: Substance use was more prevalent among schizophrenia patients (41.2%) compared to FEP patients (25.0%). In both groups, substance use was associated with increased smoking, alcohol consumption, and greater clinical severity. Specifically, FEP patients with substance use reported significantly higher depressive and negative symptoms, as well as greater illness severity. Among schizophrenia patients, substance use was correlated with elevated SAPS, SANS, and CGI-S scores, as well as higher rates of self-mutilation. Conclusion: Substance use contributes to greater symptom burden, behavioral dysregulation, and overall clinical severity in both FEP and schizophrenia. Early screening and the integration of dual-diagnosis treatment strategies are essential to mitigate adverse outcomes in psychotic disorders.